A Single Institution Experience with Solid Pseudopapillary Neoplasm of the Pancreas: Clinicopathological Correlation and Review of the Literature - Kiani, Amen Zafar; Khan, Hadi Mohammad; Ali, Zafar; Sheikh, Hasham Saleem; Khan, Adeel Shahid; Atiq, Muslim (Asian Pacific Journal of Cancer Care, 2023)
Introduction: SPN is a rare, low-grade malignancy that accounts for 1-3% of all pancreatic neoplasms and tends to affect young females. It can be asymptomatic or present with abdominal pain, and surgical resection is the only curative treatment. Methods: A retrospective study was conducted on patients with biopsy proven Solid Pseudopapillary Neoplasm (SPN) of the pancreas between January 2016 and June 2021. The study included 14 cases, including 7 resection specimens and 7 biopsies, and was conducted at a tertiary referral center in Pakistan Results: All 14 patients were female and ranged in age from 15 to 48 years old, with a mean age of 24. The most common symptom was abdominal pain, and the head of the pancreas was the most common location of the tumor. Tumor size ranged from 5 cm to 18 cm, and one patient had lymph node involvement and two patients had hepatic metastasis. Most patients received surgical treatment, and follow-up information was available for 8 out of the 14 patients, who were all alive with no recurrence or metastasis. Conclusion: Due to its rarity, non-specific clinical presentation, and imaging findings, it can be challenging to diagnose. There is a lack of data on SPN from South Asia, so this study provides valuable insights into the occurrence and treatment of SPN in this region.